Visible-light-promoted oxidation/condensation of benzyl alcohols with dialkylacetamides to cinnamides. Issue 3 (19th December 2018) - Yang, Tianlong; Lu, Maojian; Lin, Zhaowei; Huang, Mingqiang; Cai, Shunyou
Abstract : An oxidative cross-coupling reaction of benzyl alcohols with dialkylacetamides was developed to construct cinnamides under visible-light-enabled photocatalytic conditions. Abstract : Oxidative cross-coupling reactions of benzyl alcohols with N, N -dialkylacetamides were developed only employing oxygen as the terminal oxidant, efficiently providing a new, novel protocol for the construction of multifunctionalized cinnamides with the synergistic effects of KOH, organic photocatalyst eosin Y, and visible light irradiation at room temperature. A broad substrate scope and mild reaction conditions are the prominent features of this transformation.